Faktor-Faktor yang Mempengaruhi Kualitas Kerja Audit Internal: Komitmen Profesional, Time Budget Pressure, dan Budaya Organisasi - Siregar, Arninda Sekar Sari; Sembiring, Mira Octavia; Deliana, Deliana; Napitupuluh, Ilham H. (Jurnal Riset Akuntansi dan Bisnis, 2024)
Previous research or relevant research has a very important role in research or scientific articles. Relevant research is used to strengthen the theory and explain the relationship and influence between variables. In this article, a review is conducted related to the factors that affect the quality of internal audit performance, professional commitment, time budget pressure, and organizational culture based on a literature study of internal audit reviews. The purpose of writing this article is to develop hypotheses between variables that will be used in future research. The results of the literature review in this article are: 1) Professional commitment affects the quality of internal audit work, 2) Time budget pressure affects the quality of internal audit work, and 3) Organizational culture affects the quality of internal audit work.